Preclinical characterization of ISB 1342, a CD38 × CD3 T-cell engager for relapsed/refractory multiple myeloma - Pouleau, B; Estoppey, C; Suere, P; Nallet, E; Laurendon, A; Monney, T; Pais Ferreira, D; Drake, A; Carretero-Iglesia, L; Macoin, J; Berret, J; Pihlgren, M; et al. (American Society of Hematology, 2023)
Although treatment of multiple myeloma (MM) with daratumumab significantly extends the patient's lifespan, resistance to therapy is inevitable. ISB 1342 was designed to target MM cells from patients with relapsed/refractory MM (r/r MM) displaying lower sensitivity to daratumumab. ISB 1342 is a bispecific antibody with a high-affinity Fab binding to CD38 on tumor cells on a different epitope than daratumumab and a detuned scFv domain affinity binding to CD3ε on T cells, to mitigate the risk of life-threatening cytokine release syndrome, using the Bispecific Engagement by Antibodies based on the TCR (BEAT) platform. In vitro, ISB 1342 efficiently killed cell lines with different levels of CD38, including those with a lower sensitivity to daratumumab. In a killing assay where multiple modes of action were enabled, ISB 1342 showed higher cytotoxicity toward MM cells compared with daratumumab. This activity was retained when used in sequential or concomitant combinations with daratumumab. The efficacy of ISB 1342 was maintained in daratumumab-treated bone marrow patient samples showing lower sensitivity to daratumumab. ISB 1342 induced complete tumor control in 2 therapeutic mouse models, unlike daratumumab. Finally, in cynomolgus monkeys, ISB 1342 displayed an acceptable toxicology profile. These data suggest that ISB 1342 may be an option in patients with r/r MM refractory to prior anti-CD38 bivalent monoclonal antibody therapies. It is currently being developed in a phase 1 clinical study.